Service quality assessment in liner shipping industry: an empirical study on Asian shipping case - Huang, Sheng Teng; Bulut, Emrah; Duru, Okan (INDERSCIENCE ENTERPRISES LTD, 2015)
The aim of this paper is to improve service quality of liner shipping companies and investigates the quality function deployment (QFD) in terms of quality assessment method. Liner shipping is particularly characterised by the container transportation and the wider organisation including other logistics activities. The major customers of the logistics services are the industrial clients. The customer satisfaction is a key managerial task since competitiveness is a growing issue in the liner shipping industry. The QFD is one of the unique procedures to expose the requirements of customer and transform them into managerial tasks by cross-correlation analysis between requirements and technical measures. The empirical study is performed to investigate service quality of Asian liner shipping industry by focusing on a group of anonymous leading liner shipping companies. One of the major finding is the customer of liner shipping service tends to purchase a complete transport service including other logistics services. The important technical measures are the implementation of ISO 9001 framework, cheaper service and exemption on terminal handling fee.
Keywords: quality function deployment; house of quality; HoQ; liner shipping; service quality; fuzzy analytic hierarchy process; FAHP; quality management; FUZZY-AHP; FUNCTION DEPLOYMENT; CONSISTENCY INDEX; FIRM PERFORMANCE; LOGISTICS; IMPACT; CAPABILITIES; MANAGEMENT; PRIORITIES; TOPSIS; Business & Economics; Transportation